Optimization of spatial landscape parameters using parametric design and genetic algorithm on outdoor thermal comfort in Clark Global City - Lazaro, Inigo D. (College of Architecture, University of the Philippines Diliman, 2025)
Urban development in the Philippines is rapidly expanding beyond major metropolitan areas, presenting both opportunities and challenges. While this urbanization plays a crucial role in economic growth, it also raises significant environmental concerns, particularly the urban heat island (UHI) effect. This phenomenon, intensified by the dense grey infrastructure in the Philippines, contributes to increased outdoor thermal stress, which can negatively impact the people’s well-being. Despite the urgency of addressing UHI, Clark Global City lacks comprehensive guidelines for mitigating its effects and improving outdoor thermal comfort (OTC). This study focuses on optimizing the spatial parameters of urban influences on OTC. The objective is to achieve adequate thermal comfort while considering the unique climatic conditions of the Philippines. To identify the relevant parameters, a review of prior research was conducted, highlighting effective strategies already implemented in similar contexts. Using Rhino 3D software and the Grasshopper interface, the researcher modeled these parameters parametrically. The study employed a single-objective genetic algorithm with the Galapagos component, allowing for the exploration of different parameter influences on thermal comfort. The results of the optimization process yielded an enhanced urban model with increased open space coverage and tree cove of 15 percent and 20 percent, respectively. This improved the overall thermal comfort of the site at 9:00am by increasing the percentage of areas with a moderate heat stress level to 62.10 percent from 52.40 percent. The findings underscore the importance of integrating cooling strategies into urban planning to foster sustainable development.